A qualitative interview study into experiences of management of labor pain among women in midwife-led care in the Netherlands - Trudy Klomp; Anke B. Witteveen; Ank de Jonge; Eileen K. Hutton; Antoine L. M. Lagro-Janssen (Taylor & Francis Group, 2017)
Introduction: Many pregnant women are concerned about the pain they will experience in labor and how to deal with this. This study's objective was to explore women's postpartum perception and view of how they dealt with labor pain. Methods: Semistructured postpartum interviews were analyzed using the constant comparison method. Using purposive sampling, we selected 17 women from five midwifery practices across the Netherlands, from August 2009 to September 2010. Results: Women reported that control over decision making during labor (about dealing with pain) helped them to deal with labor pain, as did continuous midwife support at home and in hospital, and effective childbirth preparation. Some of these women implicitly or explicitly indicated that midwives should know which method of pain management they need during labor and arrange this in good time. Discussion: It may be difficult for midwives to discriminate between women who need continuous support through labor without pain medication and those who genuinely desire pain medication at a certain point in labor, and who will be dissatisfied postpartum if this need is unrecognized and unfulfilled.